A new species of the Gonyosoma prasinum species complex (Squamata: Serpentes: Colubridae) from Indochina - Poyarkov, Nikolay A.; Bragin, Andrey M.; Idiiatullina, Sabira S.; Tran, Tuan Anh; Le, Dac Xuan; David, Patrick; Nguyen, Tan Van (Zootaxa, 2025)
A new species of the genus Gonyosoma Wagler is described from Vietnam and Laos, based on an integrative approach combining morphological and molecular evidence. Gonyosoma iadinum sp. nov. is distinguished from its congeners by a unique combination of diagnostic characters. It differs from its morphologically closest relative, Gonyosoma coeruleum Liu, Hou, Lwin, Wang & Rao, in the structure of the cloacal plate and hemipenes, as well as in significant genetic divergence in the cytochrome b (cyt b) mitochondrial DNA (mtDNA) gene sequences (p > 8.1%). The new species is currently known from central and southern Vietnam and central and southern Laos, where it has been recorded in montane evergreen forests of the Kon Tum-Gia Lai Plateau and the Langbiang Plateau in Vietnam. In Laos, it has been documented in Khammouan Province and the Bolaven Plateau. The species inhabits elevations ranging from 655 to 1,550 m above sea level. Further studies are required to reassess the taxonomic status of the Gonyosoma prasinum complex, particularly in Hainan Island, China. Based on its known distribution and available data, we suggest that the new species should be classified as Least Concern (LC) under the IUCN Red List criteria. We also provide an updated taxonomic key for the Gonyosoma species.